Kebijaksanaan dan Perspektif Penelitian dan Pengembangan Pertanian dalam Mendukung Otonomi Daerah - Tahlim Sudaryanto; I Wayan Rusastra (Forum penelitian Agro Ekonomi, 2000)
EnglishThe role of regional government on agricultural development management will be very important by the implementation of UU No.22/1999 and UU No.25/1999. On the spirit of autonomy, the local government is still needed to consider and accommodate some of national agricultural development strategy such as considering agricultural on transforming economic structure, enhancing sustainable food security, agribusiness and agropolytan development adapted for the benefit of regional development as well as the welfare of the local people. In this case, AIAT played an important role through focusing on resource based agricultural development supporting by location specific technology in order to have higher financial and economic efficiency. During the transision period, technical, management, and financial support from central government are necessary, especially for the region having budget constraint and limited capacity of human resource development. For the perspective of autonomy, AIAT or Agency for Regional Research and Development (Balitbangda) have to strenghten participative research planning program and its implementation through empowering interregional research coordination, human resource development, and condusive insentive system. IndonesianImplementasi UU No.22/1999 dan UU No.25/1999 memberikan implikasi strstegis mengenai peran daerah dalam menejemen pembangunan termasuk di dalamnya pembangunan pertanian. Dalam semangat otonomi daerah, pemerintah setempat perlu tetap mengacu dan mengakomondasi beberapa strategi pembangunan pertanian nasional seperti transformasi struktur ekonomi berbasis pertanian, peningkatan ketahanan pangan berkelanjutan, pengembangan agribisnis dan ekonomi kerakyatan, dan pengembangan agropolitan yang diadaptasikan bagi pembangunan daerah dan kesejahteraan masyarakat setempat. Balai pengkajian Teknologi pertanian (BPTP) memegang peranan penting melalui pengembangan komoditas unggulan lokal yang didukung teknologi spesifik lokasi dan sesuai dengan potensi sumber daya dan keunggulan komparatif wilayah. Dalam masa transisi ini, dukungan bimbingan teknis, menejemen, dan pendanaan dari pusat masih tetap di perlukan, khususnya bagi daerah yang terbatas kemampuan sumber daya manusia (SDM) dan keuangannya. Dalam perspektif otonomi daerah, BPTP/Balitbangda perlu memperkuat perencanaan dan pelaksanaan seluruh program penelitian/pengkajian partisipatif, dengan penguatan koordinasi penelitian antar wilayah, pengembangan SDM dan sistem insentif yang handal.